The Creation of Campus Cafe in Getting Profit - Fitri Hayati (Budapest International Research and Critics University, 2019)
The culinary business recently becoming trend is blocked by people. Café is a vehicle for people to gather, play and work and so on. Attractive offers are always served at Cafés ranging from food and drinks with unique variations in accordance with the café theme itself. This cafe business has become a business attraction. This is because people are more comfortable in the café for more relaxed activities. Café is also a flexible place for everyone. In addition to its convenient location, the café also often offers Free WIFI. The aim of research is to find a successful method of running a café business with limited business capital. The research method is a qualitative method. The researcher examined the success tips used by the Campus Cafe on Selamat Ketaren Street No.1 and 2, Percut Sei Tuan, Medan City, North Sumatra 20371 with the name of the owner of Sultoni's brother. This cafe is just the grief of the owner, starting from unsold merchandise until employee changes. Not infrequently also the owner suffered a loss. But now this Campus Cafe has started to develop rapidly. Its existence has begun to compensate for the cafes around Jalan Selamet Ketaren, especially the Aceh Corner, which is always crowded with customers. It operates for approximately 3 years.